2014
DOI: 10.1080/10810730.2013.837551
|View full text |Cite
|
Sign up to set email alerts
|

Public Estimates of Cancer Frequency: Cancer Incidence Perceptions Mirror Distorted Media Depictions

Abstract: Compared with incidence rates, certain cancers are over- or underrepresented in news coverage. Past content analytic research has consistently documented these news distortions, but no study has examined whether they are related to public perception of cancer incidence. Adults (N = 400) completed a survey with questions about perceived cancer incidence, news consumption, and attention to health news. Cancer incidence perceptions paralleled previously documented news distortions. Overrepresented cancers were ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…60 Distortion of patients' perceptions that is induced by news coverage regarding the frequency and severity of the disease has been observed in patients with many types of tumors. 61 As detection of well-differentiated thyroid cancer in the population increases, awareness also rises. This awareness forces further investigation, which snowballs the rates of detection further.…”
Section: Patients' Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Distortion of patients' perceptions that is induced by news coverage regarding the frequency and severity of the disease has been observed in patients with many types of tumors. 61 As detection of well-differentiated thyroid cancer in the population increases, awareness also rises. This awareness forces further investigation, which snowballs the rates of detection further.…”
Section: Patients' Beliefsmentioning
confidence: 99%
“…It has been suggested that a vicious circle exists between the information that patients receive from the media or community and the discovery of subclinical disease . Distortion of patients' perceptions that is induced by news coverage regarding the frequency and severity of the disease has been observed in patients with many types of tumors . As detection of well‐differentiated thyroid cancer in the population increases, awareness also rises.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PPEH-related topics have received very limited attention. To address these gaps, we adopt an approach used in cancer communication studies (i.e., Jensen et al, 2014; Stryker, Moriarty, & Jensen, 2008) combining content analysis data from what are sometimes called ‘information-oriented media sources’ (e.g., news stories, magazines, the Internet; Dutta-Bergman, 2004) with a survey of the target population: new and expectant mothers.…”
mentioning
confidence: 99%
“…Previous analyses have observed that the distribution of news stories by cancer anatomical site mirrors incidence rates more closely than mortality rates but that certain cancer types were overor under-represented. These distortions, potentially driven by personalisation bias (e.g., celebrity profiles) were also reflected in risk perception and discrepancies in funding for cancer research [13][14][15]. Others have also documented variation in quality, topic coverage and style of cancer research reporting in print media [16][17][18].…”
Section: Introductionmentioning
confidence: 99%